The role of knowledge about generative ai on decision-making among leaders in public universities - Safiah Masbaka; Jamsari Hashim; Farous Izwan Abdul Aziz; Syahrul Nizam Salam (Penerbit Universiti Malaysia Sabah, 2024)
This conceptual paper discusses the roles of knowledge about generative artificial intelligence (GAI) on decision-making among leaders in public universities. This paper uses literature review technique. The result of this discussion is the roles of GAI knowledge on decision-making from the perspective of leaders in public universities among members of the senate and top management. GAI helps to automate the creation of digital content that transforms teaching and learning, research, and academic publishing paradigms in public universities. Leaders in public universities equipped with knowledge of GAI’s transformative potentials as well as its disruptive risks can leverage their strategic positions to plan and manage university governance frameworks for the ethical use of AI in higher learning institutions. They can involve stakeholders from the government, academia, industry, and society, to harness the benefits of GAI technology ethically to enhance research, publication, as well as teaching and learning while managing its inherent risks. Their decisions steer the ethical integration and adoption of technology into the academic functions in higher learning institutions in the University 4.0 era. This paper suggests the need for an empirical case study on the successful implementation of GAI regulations in academia from the perspective of educational leaders.